E-learning: a practical solution for training and tracking in patient-care settings. - Nelson EA (Nursing Administration Quarterly)
E-learning, online computer (Web)-based educational training, may be the solution to keeping health care staff abreast of new technologies, information, and regulations. Compared with traditional classroom teaching, e-learning can deliver content faster to the entire staff, be individualized to meet pace, language, and reading level. Additionally, an e-learning system provides accurate and automatic tracking. Although some teaching methodologies are key to ensuring learning (i.e., skills' demonstration or practicing negotiation skills), e-learning can decrease time away from work by providing essential information and content.